Issues of Business Education in the 21st Century: Demonstrating the Learning and Spreading Skills - Garg, Navin Kumar; Garg, Aditi (Journal of Commerce and Trade, 2007)
India has recognized education as a medium to prepare people for effective role they play in the society for the setup of sound democratic system. It is the best investment that any nation could make for the benefit of its citizens. With the changing face of the business world, the role of business schools in delivering business education also demands restructuring. The present education in business pays attention more on the materialistic progress of individual and enterprise. It is concluded here that the proper implementation of technology will prepare us to exploit fresh opportunities created by the new environment. The vulnerable changes in the business world can be imbibed into the education system for meeting the challenges.